PREDICTION OF LIVER FIBROSIS IN CHRONIC VIRAL HEPATITIS C IN HIV-INFECTED - Rakhimova Aziza Fakhriddinovna (Modern American Journals, 2025)
Liver lesions in children with HIV infection remain a pressing problem due to the frequency of their occurrence and the diverse etiology of the diseases. HIV is considered the cause of many hepatobiliary disorders; hepatotropic effects can be exerted by: chronic viral hepatitis B and C, opportunistic infections, in addition, there is a direct effect of the human immunodeficiency virus and the hepatotoxic effect of antiretroviral therapy (ART) drugs.
Keywords: HIV, infection, viral hepatitis, treatment, liver